Variations of Signal Strength during Solar Bursts: A Probable Coronal and Surface Effects of the Sun (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Variations of signal strengths during solar bursts recorded at Kalyani corresponding to two different frequencies, 406.7 MHz and 100 MHz are reported.  The amplitude of the signals received at 406.7 MHz is found larger and that the flares analyzed are mostly of M-type. The signal strengths of the coronal effect at such times were very high compared to the surface effect of the Sun. The signal level of surface effect of the Sun at the peak activity varies in amplitude from 0.06 volts to 0.1 volt while those related to solar corona vary in between 7.0 to 7.2 volts. Both the solar wind velocity and proton density are found to increase in the dates of severe bursts and there are sudden disturbances in the arrival direction of solar wind particles. Also the geomagnetic indices are enhanced at the time of solar bursts when the DST index reduces rapidly.